Outcomes of transperineal reanastomosis as a salvage treatment for recurrent vesicourethral anastomosis stenosis after radical prostatectomy - Piotr Gwara; Łukasz Białek; Marta Rydzińska; Jakub Dobruch; Michał Andrzej Skrzypczyk (Archivio Italiano di Urologia e Andrologia, 2024)
Purpose: To evaluate transperineal reanastomosis (TRPA) combined with incontinence surgery as a complex treatment for recurring vesicourethral anastomosis stenosis (VUAS) after radical prostatectomy (RP). Methods: Retrospective analysis of 8 patients who underwent TRPA for recurring VUAS. Detailed preoperative and follow up data were assessed. Results: Mean follow up lasted 47 months (range 17-77) with mean age being 63.4 years (range 61-70). All patients achieved patency and 87.5% (7/8) maintained it to the end of follow up. However, four of them required additional procedures to retain patency. Six underwent incontinence surgery – artificial urinary sphincter (AUS) implantation – after which one cuff erosion occurred. In the end 62.5% (5/8) of patients achieved patent urethra and continence. Conclusions: TRPA combined with incontinence surgery is a reasonable treatment for patients with recurrent VUAS. Nonetheless, this is a set of difficult surgeries that may ultimately end in failure, i.e. the inability to restore urethral patency, urinary incontinence or urinary diversion, hence they should be performed by experienced surgeons.